Hyperpolarization of sup3He nuclei - Jug, Matevž (Matrika, 2021)
Highly polarized ?$^3$?He gas is a versatile substance, with uses spanning from fundamental physics research to medical diagnostics. Two potent methods of its production, spin-exchange optical pumping and metastability-exchange optical pumping will be presented, with a focus on the first one. A slowly emerging but very promising application of polarized ?$^3$?He is in magnetic resonance imaging of the lungs, which will also be discussed.
Keywords: helij; helium; Highly polarized nuclei; magnetic resonance; magnetna resonanca; močno polarizirana jedra; optical pumping; optično črpanje